Creating literacy-rich schools for adolescents - Ivey, Gay (Association for Supervision and Curriculum Development, 2006)
Gay Ivey and Douglas Fisher give educators practical strategies to help motivate secondary students to embrace reading, writing, listening, and speaking as essential skills for learning and thinking throughout their lives.